2005
DOI: 10.1111/j.1444-2906.2005.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers derived from bay scallop Argopecten irradians expressed sequence tags

Abstract: When data mining was performed on the National Center for Biotechnology Information database, a total of 2038 sequences from five different expressed sequence tag libraries were registered. Eighty sequences (3.9%) were found to contain 91 microsatellites. Clustering analysis indicated that 23 sequences of these expressed sequence tags fell into five clusters and that the remaining 57 sequences were independent. The di-and tri-nucleotide repeat motifs accounted for approximately 62.1% of the total microsatellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 21 publications
4
52
0
Order By: Relevance
“…No successful amplification was detected in P. albicans samples. Poor microsatellite transferability among related species has also been observed in previous studies in marine bivalves (Zhan et al 2005;Hedgecock et al 2004). …”
mentioning
confidence: 67%
“…No successful amplification was detected in P. albicans samples. Poor microsatellite transferability among related species has also been observed in previous studies in marine bivalves (Zhan et al 2005;Hedgecock et al 2004). …”
mentioning
confidence: 67%
“…black tiger shrimp (Penaeus monodon) (13.7%, Maneeruttanarungroj et al, 2006), Japanese pufferfish (Fugu rubripes) (11.5%, Edwards et al, 1998) and channel catfish (11.2%, Serapion et al, 2004), but higher than those in some other species e.g. Chinese shrimp (Fenneropenaeus chinensis) (2.2%, Wang et al, 2005), bay scallop (Argopecten irradians) (3.9%, Zhan et al, 2005), and red sea bream (Chrysophrys major) (4%, Chen et al, 2005). The abundance of EST-derived microsatellites seems to be highly species-specific in aquacultured animals studied.…”
Section: Discussionmentioning
confidence: 99%
“…Since Serapion et al (2004) first demonstrated the development of Type I marker (EST-SSRs) in an aquaculture species by using bioinformatic analysis, mining EST-SSRs from EST databases have been reported in several other aquaculture animals including fish (Yue et al, 2004;Rexroad et al, 2005;Chen et al, 2005), shrimp Pérez et al, 2005;Maneeruttanarungroj et al, 2006) and scallop (Zhan et al, 2005). Online resources of EST sequences have been increasingly accumulated in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers, especially microsatellites, are effective markers that have been widely applied to the development of marker-assisted breeding technology and conservation of this species, because of the high degree of polymorphism, abundance, neutrality, and codominant inheritance (Zhan et al, 2005;Schwartz et al, 2007). Therefore, the development of new polymorphic microsatellite markers opens new perspectives for population genetics (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%